DEVELOPMENT OF STEM-BASED DIGITAL POCKETBOOK ON SPLDV MATERIAL USING THE ADDIE MODEL: APPLICATION IN ONLINE LEARNING ENVIRONMENTS - Komarudin, Komarudin; Suherman, Suherman; Puspita, Laila (FKIP Universitas Muhammadiyah Tangerang, 2024)
This study aims to assess the feasibility, teacher and student responses, and effectiveness of the STEM-based digital pocketbook on the topic of Systems of Linear Equations in Two Variables (SPLDV). The subjects of this research were junior high school students in Bandar Lampung. Data collection instruments included questionnaires distributed to subject matter experts, media experts, and student respondents. The method in this research uses the ADDIE model which consists of 5 stages, namely: Analysis, design, development, implementation, and evaluation. The findings indicate that the developed learning media are highly suitable and engaging for mathematics instruction, particularly concerning SPLDV topics. However, due to the global COVID-19 pandemic, the research did not progress to the implementation phase, thereby precluding the effectiveness testing of the STEM-based digital pocketbook